Determinação voltamétrica de resíduos do herbicida Glifosato em águas naturais utilizando eletrodo de cobre - Garcia, Andresa Fabiana (2006)
Glyposate has been widely used in different countries, and the presence of this herbicide in surface waters has received great attention in the last decade. With the increase in environmental concern considerable attention has been given to the development of reliable methods for glyphosate determination. Glyphosate is not electroactive with the Hg electrode and its determination with this electrode needs preliminary reactions. Therefore, the aim of this work was to investigate the Copper electrode response in the voltammetric determination of glyphosate. This response is produced by complexation of glyphosate with cupric ions in the outer, porous layer. The best analytical conditions for the voltammetric determination are: phosphate buffer 0.05 mol L-1 I and pH 7.3. The limit of detection and the limit of quantification are, respectively, 59 µg L-1 e 196 µg L-1, and these values indicate the potential use of the proposed method in the glyphosate determination in natural waters. The method was compared to another voltammetric method with Hg electrode, ater reaction with nitrite. The glyphosate concentrations found by the two methods agree very well (t test). Therefore, the proposed method can be applied to direct determinations of the herbicide in waters, decreasing the time of analysis; besides, the method is in agreement with the "green chemistry" concept.